1989
DOI: 10.1002/jlb.45.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Tumor Necrosis Factor Alpha-Induced Lymphopenia, Neutropenia, and Biphasic Neutrophilia: A Study of Lymphocyte Recirculation and Hematologic Interactions of TNFα With Endogenous Mediators of Leukocyte Trafficking

Abstract: Tumor necrosis factor alpha (TNF) induces lymphopenia, neutropenia, and biphasic neutrophilia after intravenous injection of 3,000 U TNF in Lewis rats. The mechanism of TNF-induced lymphopenia was investigated by means of thoracic duct cannulation. Hourly measurements of lymphocyte recirculation via the thoracic duct failed to reveal any significant decrease in lymphocyte recirculation in TNF-treated vs. control rats, suggesting that a decrease in lymphocyte recirculation through the thoracic duct is not the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 0 publications
2
30
1
Order By: Relevance
“…No such effect was observed in IFN-␥-knockout mice, suggesting that the IL-18-induced reduction in the number of leukocytes was mediated by IFN-␥. IL-18 has been reported to induce TNF-␣, which has been reported to cause a reduction in the number of circulating lymphocytes 6 h after administration in rats (25,31). In this study, however, we found no induction of TNF-␣ in the serum samples of mice treated with IL-18 (data not shown), suggesting that it was unlikely that TNF-␣ was involved in IL-18-induced leukocyte reduction.…”
Section: Discussioncontrasting
confidence: 70%
“…No such effect was observed in IFN-␥-knockout mice, suggesting that the IL-18-induced reduction in the number of leukocytes was mediated by IFN-␥. IL-18 has been reported to induce TNF-␣, which has been reported to cause a reduction in the number of circulating lymphocytes 6 h after administration in rats (25,31). In this study, however, we found no induction of TNF-␣ in the serum samples of mice treated with IL-18 (data not shown), suggesting that it was unlikely that TNF-␣ was involved in IL-18-induced leukocyte reduction.…”
Section: Discussioncontrasting
confidence: 70%
“…The first peak of IL-6-induced neutrophilia is therefore most likely due to demargination of peripheral neutrophils. This is consistent with the observation that the magnitude of this neutrophilia is very similar to that induced by epinephrine, a known demarginating agent in rats (77,78).…”
Section: Cytokine Effects On Leukocytessupporting
confidence: 91%
“…TNF-␣ activates neutrophils, causing their margination to the vascular wall and promoting a prothrombotic condition. [65][66][67][68] Similarly, prolonged hypoxia followed by reoxygenation triggers myriad biologic responses. [69][70][71][72] The PAR-1 agonist peptide that we used does not activate neutrophils or cause their margination.…”
Section: Discussionmentioning
confidence: 99%